2007
DOI: 10.1242/jeb.02753
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy block by MHC class I peptides is mediatedviathe production of inositol 1,4,5-trisphosphate in the mouse vomeronasal organ

Abstract: SUMMARY The vomeronasal organ (VNO) has evolved to link an animal's behavior to its environment in a highly species-specific fashion. In mice, it is thought to be the primary sensory system responsible for the detection of pheromones. Pheromones regulate a variety of responses including mate recognition in the context of selective pregnancy failure. MHC (major histocompatibility complex)class I peptides have been identified as compounds that elicit the pregnancy block effect via the VNO. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 44 publications
(58 reference statements)
1
20
0
Order By: Relevance
“…Moreover, a recent study called these findings into doubt by showing that, contrary to Hilda Bruce’s original finding, urine from castrated or juvenile males was sufficient to induce pregnancy block. These results suggest that, although volatiles can contribute to the occurrence of pregnancy block, they are not necessary to induce it 63 .…”
Section: Mhc As a Signal In Individual Recognitionmentioning
confidence: 80%
See 1 more Smart Citation
“…Moreover, a recent study called these findings into doubt by showing that, contrary to Hilda Bruce’s original finding, urine from castrated or juvenile males was sufficient to induce pregnancy block. These results suggest that, although volatiles can contribute to the occurrence of pregnancy block, they are not necessary to induce it 63 .…”
Section: Mhc As a Signal In Individual Recognitionmentioning
confidence: 80%
“…A more recent study, however, found that peptides alone (administered more frequently than in Ref. 7 ) were sufficient to induce pregnancy block 63 . These studies show that the suite of peptides presented by an individual’s MHC molecules can, when excreted in urine, be used as odorants in chemical signaling.…”
Section: Mhc As a Signal In Individual Recognitionmentioning
confidence: 93%
“…Leinders-Zufall et al 23 ), that is, some VSNs do not seem to recognize all peptides bearing the same MHC anchor residues as a single entity. So far, evidence that MHC ligands serve as signals in the sensory evaluation of genotype rests on studies of the pregnancy block, which have shown that three synthetic peptides (each at 10 À 4 M) of foreign but not self MHC type in the presence 21,53 or absence of urine 53 result in pregnancy failure.…”
Section: Discussionmentioning
confidence: 99%
“…However, the relevance of these experiments for individual recognition under natural conditions is problematic considering the non-physiologically high concentration of 10 −4  M for each peptide used in these studies. Finally, the requirement of urine as an additional stimulus in these experiments requires clarification, because in the first study [25], three peptides were applied within urine while a more recent paper described an effective pregnancy failure using only one of these peptides in the absence of urine [38]. From a theoretical point of view, it appears very puzzling that an MHC peptide ligand should exert a biological effect independent of its biochemical context.…”
Section: The Search For Mhc-dependent Peptidesmentioning
confidence: 99%